Capsule dynamics, implantation, and explantation of the smaller incision, new-generation implantable miniature telescope: a miyake-apple study - Hammer, Maximilian; Schickhardt, Sonja; Zhang, Lu; Munro, Donald; Yildirim, Timur Mert; Auffarth, Gerd U. (Retina, 2023)
Purpose: - The smaller incision, new-generation implantable miniature telescope is a novel implant to optimize vision in retinal patients with central vision loss. Using Miyake-Apple techniques we visualized the device implantation, repositioning, and explantation, while noting capsular bag dynamics. - Methods: - Using the Miyake-Apple technique, we assessed capsular bag deformation after successful implantation of the device in human autopsy eyes. We assessed rescue strategies for converting a sulcus implantation to a capsular implantation and explantation strategies. We noted the occurrence of posterior capsule striae, zonular stress, and the haptics' arc of contact with the capsular bag after implantation. - Results: - Acceptable zonular stress was observed during the successful implantation of the SING IMT. When it was implanted in the sulcus, one could reposition the haptics into the bag with two spatulas using counter-pressure in an effective strategy despite inducing tolerable, medium zonular stress. A similar technique, in reverse, allows safe explantation without damaging the rhexis or the bag, while inducing similar medium, tolerable zonular stress. In all eyes we examined, the implant considerably stretches the bag, inducing a capsular bag deformation and posterior capsule striae. - Conclusion: - The SING IMT can be safely implanted without significant zonular stress. In sulcus implantation and explantation, repositioning of the haptic is achievable without perturbing zonular stress using the presented approaches. It stretches average-sized capsular bags to support its weight. This is achieved by an increased arc of contact of the haptics with the capsular equator.